A web-based diagnostic reference centre for the European Reference Network "EpiCare": recommendations of the eNeuropathology working group - Kölble, Konrad; Cross, J. Helen; Becker, Albert; Blümcke, Ingmar (Epileptic Disorders, 2018)
Epilepsy surgery is a valuable treatment strategy for a selected group of patients with drug-resistant focal epilepsy. While reliable disease classification is essential for the optimal management of patients in general and crucial for the development of more personalized therapies in the future, arriving at a precise diagnosis often poses considerable difficulties due to the broad and variant-rich spectrum of epilepsy-associated brain lesions. Given the scarcity of European institutions diagnostically focusing on the histopathology of epilepsy surgery cases, the provision of subspecialty expertise as well as training opportunities remains logistically and financially challenging. To improve this situation, the European Reference Network's (ERN) epilepsy care program (EpiCare, http://epi-care.eu) has set out to develop a web-based microscopy referral and teaching framework. This paper reviews the aspects of digital microscopy, data storage, and image analysis technology relevant to the practice of neuropathology. Cognizant of the European data security requirements and regulations, we propose a collaborative, diagnostic network initiative (the eNeuropathology reference centre) and delineate a roadmap for its implementation favouring open-source, vendor-independent browser platforms.
EVALuna2:36582